Ups and Downs across Central and Eastern Europe - Slantcheva-Durst, Snejana (International Higher Education, 2010)
Larger private higher education sectors are much more common across central and eastern Europe. After the fall of the communist regimes in 1989, private institutions of higher education multiplied to varying degrees in central and eastern Europe. The most recent trendsreveal slow private growth in most of these countries. Declines in the number of people served by private institutions have been limited in range and time, yet have occurred in both the university and nonuniversity private sectors.